A strategy to improve arithmetical performance in four day-old domestic chicks (Gallus gallus). Issue 1 (December 2017) - Rugani, Rosa; Loconsole, Maria; Regolin, Lucia
Abstract A large body of literature shows that non-human animals master numerical discriminations, but a limit has been reported in a variety of species in the comparison 3vs .4. Little is known regarding the possibility of using "cognitive strategies" to enable this discrimination. The aims of this study were to investigate: whether domestic chicks discriminated 3vs .4, and if changes in stimuli presentation could improve chicks' numerical performance. Newly hatched chicks were reared with seven identical objects. On day 4, they underwent 20 consecutive testing trials to assess their capability to discriminate 3vs .4. The objects were presented, one-by-one, to the chicks and hidden behind one of two identical panels. As expected, the chicks did not discriminate (Experiment 1). When objects were presented and hidden in groups comprising one or two objects (2 + 1)vs .(2 + 2), the chicks succeeded (Experiment 2). The grouping strategy did not help in the case of a harder discrimination of (3 + 1)vs .(3 + 2) (Experiment 3), unless chicks were allowed to rest for two hours between testing sessions (Experiment 4). Our results suggest that in some cases, the limits reported for numerical performance in animals do not depend on cognitive limitations but on attentional or motivational factors, which can be overcome employing simple procedural adjustments.